Impact of Tb3+ ion concentration on the morphology, structure and photoluminescence of Gd2O2SO4:Tb3+ phosphor obtained using thermal decomposition of sulfate hydrate. (4th June 2020) - Rodrigues, R.V.; Marciniak, Ł.; Khan, L.U.; Muri, E.J.B.; Cruz, P.C.M.; Matos, J.R.; Strȩk, W.; Marins, A.A.L.
Abstract: Gadolinium oxysulfate doped with terbium (Gd2 O2 SO4 :Tb 3+ ; 0.1, 1.0, and 10.0 mol%) materials were obtained using thermal decomposition from sulfate hydrate under a dynamic air atmosphere and between 1320–1400 K. The materials were characterized using Fourier transform infrared spectroscopy, thermogravimetric/derivative thermogravimetric investigations and X‐ray powder diffraction patterns. The Tb2 O2 SO4 compound was obtained at 1300 K and was used to compare thermal stability and photoluminescence behaviour with that of Gd2 O2 SO4 :Tb 3+ (0.1, 1.0, and 10.0 mol%). Magnetic susceptibility measurements indicated the presence of 15% Tb 4+ phases within Tb2 O2 SO4 . The materials were excited at 377 nm and displayed green narrow lines with the strongest emission peak at 545.5 nm due to the 5 D4 → 7 F5 transition of Tb 3+ ions. Brightness of terbium‐activated gadolinium oxysulfate phosphors was enhanced with increase in the concentration of Tb 3+ . Detailed analysis of spectroscopic properties of materials under investigations revealed efficient Gd2 O2 SO4 to Tb 3+ and Tb 3+ to Tb 3+ energy transfers. Increase in dopant concentration led to the enhancement of 5 D4 → 7 FJ emission intensity and reduction of 5 D3 → 7 FJ emission intensity via cross‐relaxation mechanisms. Distribution of particle size was increased by controlling dopant concentration in the host lattice. Obtained results confirmed that these materials could be applied potentially in field emission display devices and light‐emitting diodes.